Characteristic of Fatty Acids Biotransform from Hermetia Illucens Prepupae Fed with Various Organic Wastes before Conversion to Methyl Ester Form - Leong, S.Y. (Institute of Physics Publishing, 2020)
Farming of Black solder fly (Hermetia illucens) had received great research interest by scientist to investigate the application of this insect's larvae as a means of organic waste biotransformation, feed for aquaculture and husbandry as well as for biodiesel feedstock. The compositions of this insect's larvae is well known to have high content of lipid and protein, this has demonstrates its potential use as animal feed and alternative energy. To the best of our knowledge, this study provides the ultimate investigation on the characteristic of the pre-pupae fatty acids than that of the feeds before conversion to methyl ester for biodiesel production. The study also investigates the impact of different feeds on fatty acid profile of Hermetia illucens. The farming and breeding of Hermetia illucens fly lifecycle was set up and the populations were maintained at Universiti Tunku Abdul Rahman (UTAR), Kampar campus. The newly hatched neonates were fed on fruit waste and food waste, respectively. Continuous feeding was dispensed to the neonates until it became pre-pupae. At this stage, cessations of feeding and self-harvesting by the pre-pupae were observed. The harvesting of the pre-pupae was done at this instar. Thereafter, the harvested live pre-pupae were cleaned and processed into dried pre-pupae. The dried pre-pupae were kept in an air tight container for further use. The characteristic of the feed and the dried pre-pupae were determined in a series of analysis such as crude lipid extraction, free fatty acid, acid value and fatty acid methyl ester analysis. All the analysis was done in accordance to AOAC methods and each analysis was repeated in triplicates. The results from the study shows that, Hermetia illucens pre-pupae crude lipids content as well as fatty acid profile was influenced by types of feeds as their diet. The lipid content found in the larvae biomass were profound regardless the types of feed. Comparatively, the amount of crude lipid obtained from Hermetia illucens pre-pupae was found to be higher than that of all feeds. The amount of crude lipids extracted from feeds of fruit waste and food waste were approximately 1.24 ± 0.06 and 3.27 ± 0.28 wt, respectively. The amount of pre-pupae's crude lipid derived from fruit waste and food waste were higher by 35.85 and 11.48 times, respectively. It is noteworthy that, increase in the lipid accumulation in larvae biomass indicates that the larvae are able to assimilate and bio-convert the feed composition into their own biomass. Consequently, the nutrient composition contains in the types of feed, ingested and digested by the larvae strongly affect the overall lipid accumulation. Moreover, the fatty acid extracted from the Hermetia illucens biomass showed approximately 1.77 times higher in saturated fatty acid (SFA) than that of fruit waste and food waste. Lauric acid is the predominant saturated fatty acid found in the prepupae. The SFA attained by the pre-pupae derived from fruit waste and food wastes were 84.7 and 81.5 wt, respectively. While the total unsaturated fatty acids were found to be higher in the feeds than that of the pre-pupae. Meanwhile, the total amount of unsaturated fatty acid from fruit waste and fruit waste were attained at 50.9 and 53.7 wt, respectively. In conclusion, the next stage of this study will be carried out to evaluate the biodiesel quality of the converted fatty acid methyl ester derived from Hermetia illucens fatty acid. © Published under licence by IOP Publishing Ltd.